EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) MELALUI GAME EDUKASI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Yulisnawati, Yulisnawati; Ita Yusritawati; Reza Muhamad Zaenal (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2025)
This study aims to determine the effectiveness of the Project Based Learning (PjBL) learning model through the educational game media snakes and ladders on students' mathematical problem-solving abilities. The background of this national research is based on the low mathematical problem-solving abilities of students as shown by international data, as well as the still dominant use of conventional learning methods that do not actively involve students. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Pretest-Posttest Control Group Design. The subjects of the study were grade VIII students at SMP Negeri 7 Kuningan in the 2024/2025 academic year, with samples consisting of two classes: an experimental class using the PjBL model through educational games, and a control class using conventional learning. Data were collected through pretest and posttest tests and student response questionnaires. The results showed that there was no significant difference in initial abilities between the two classes. However, after the treatment, there was a significant difference in the posttest results and an increase in the N-Gain score of mathematical problem solving ability between the experimental and control classes, which were analyzed using the Mann Whitney U non-parametric test. In addition, the results of the questionnaire showed that students gave a positive response to learning with the PjBL model through the snake and ladder educational game, with an average percentage of 75.025% in the high category. Thus, it can be concluded that the PjBL model through educational games is effective in improving students' mathematical problem solving abilities and is able to create a fun and interactive learning atmosphere.